TET3 Protein Represses Proliferation of the MG-63 Human Osteosarcoma Cell Line by Regulating DNA Demethylation: an Epigenetic Study - Hang, Shijun; Cui, Bingjun; Wei, Aichun; Li, Zi; Sun, Haitao (Folia biologica, 2024)
Recent studies have highlighted the significant role of 5-hydroxymethylcytosine (5hmC) in carcinogenesis. However, the specific role of 5hmC in osteosarcoma (OS) remains largely unexplored. The-re-fore, this study aimed to investigate the function of 5hmC and TET3 in OS. In this study, we found a decreased total level of 5hmC in OS tissues. The expression of the TET3 protein was also decreased in OS. Importantly, the decreased levels of TET3 were associated with a decreased disease-free survival (DFS) rate in patients. To investigate the role of TET3 and 5hmC in OS, we manipulated the levels of TET3 in MG-63 cells. Silencing TET3 in these cells resulted in a twofold increase in proliferation. Additio-nally, the level of 5hmC decreased in these cells. Con-versely, over-expression of TET3 in MG-63 cells led to the expected inhibition of proliferation and invasion, accompanied by an increase in 5hmC levels. In conclusion, both 5hmC and TET3 protein levels were decreased in OS. Additionally, the over-expression of TET3 inhibited the proliferation of MG-63 cells, while the suppression of TET3 had the opposite effect. These findings suggest that decreased levels of 5hmC and TET3 may serve as potential markers for OS.
Keywords: 5hmC; regulace genové exprese u nádorů; osteosarkom; Humans; Epigenesis, Genetic; nádory kostí; 5-methylcytosin; Female; Bone Neoplasms; Osteosarcoma; lidé; proliferace buněk; protoonkogenní proteiny; DNA Demethylation; epigeneze genetická; ženské pohlaví; Male; Cell Proliferation; demetylace DNA; 5-Methylcytosine; dioxygenasy; Proto-Oncogene Proteins; Dioxygenases; nádorové buněčné linie; Cell Line, Tumor; mužské pohlaví; Gene Expression Regulation, Neoplastic; TET3